KOMPARATIVNA ANALIZA PROJEKTNOG FINANSIRANJA - Mihajlovic, Milan; Zupur, Milenko; Zekić, Miodrag; Janjetović, Maja (International Journal of Economic Practice and Policy, 2025)
In market economies, companies always evaluate the effect of long-term capital investments, that is, the net cash flow that is realized during the exploitation of the investment project. The importance of this topic is reflected in the fact that when evaluating investment projects, insufficient attention is still paid to social profitability and the impact of the project on, for example, the current account of the balance of payments. The analysis of the social profitability of the project refers to the determination of the investment project’s contribution to the development of the national economy. A few projects, individually analyzed, can reject positive financial results, that is, high returns on own capital during exploitation, but as a whole, these projects can have a very negative impact on the foreign trade balance. Social Cost Benefit Analysis, also known as economic analysis, is seen as an opportunity to expand the scope of financial analysis, based on the structure of the project’s gross cash flow. A well-executed social Cost Benefit analysis can divide the net benefit of an investment project into the investor’s financial benefit and the state’s financial benefit.